1. выполните умножение:
(x + y)(x - y) = x² - y²
1) (x + y)(x - y) = x² - y²
2) (k - 2)(k + 2) = k² - 4
3) (4 + b)(4 - b) = 16 - b²
4) (1/7 + x)(1/7 - x) = 1/49 - x²
5) (5/6 + m)(5/6 - m) = 25/36 - m²
6) (k + 1,1)(k - 1,1) = k² - 1.21
2. Разложите на множители:
По формуле:
x² - y² = (x - y)(x + y)
1) a² - 49 = (a - 7)(a + 7)
2) c² - 2,25 = 0,25 × (4с² - 9) = 0,25 × (2c - 3)(2c + 3)
3) 64/81 - x² = 1/81 × (64 - 81x²) = 1/81 × (8 - 9x)(8 + 9x)
4) z² - 169/196 = 1/196 × (196z² - 169) = 1/196 × (14z - 13)(14z + 13)
5) 25x² - 36 = (5x - 6)(5x + 6)
6) 0,64 - 1/9z² = 16/25 - 1/9z² = 1/225 × (144 - 25z²) = 1/225 × (12 - 5x)(12 + 5x)
(X^3+5x^2)-(x+5)=0
x^2(x+5)-(x+5)=0
(x+5)(x^2-1)=0 x1=-5 x2= -1 x3= 1
проверка
x1=-5
(-5)^3+5(-5)^2-(-5)-5=0 -125+125 +5-5 =0
x2= -1
(-1)^3+5(-1)^2-(-1)-5=0 -1+5 +1-5 =0
x3= 1
(1)^3+5(1)^2-(1)-5=0 1+5 -1-5 =0